Compaction Trends of Shales: Rock Physics and Petrophysical Properties - Beloborodov, Roman (Curtin University, 2017)
Shale is the most abundant and the least known type of sedimentary rock. It is found in every basin associated with hydrocarbon depositions and is notorious for its complicated properties. This thesis is dedicated to investigation of the compaction trends of rock physics and petrophysical properties of shale. It is supplemented with in-depth analysis of shale microstructure as a key parameter controlling the macroscopic anisotropic properties of shale.